(untitled) (Medical Forum Monthly, 2024)
Objective: The Objectives of this study was to determine mean visibility of maxillary and mandibular anterior six teeth among the patients at rest position of lips. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the at the Prosthodontics department of Liaquat Medical University from March 2022 to December 2022. Methods: A total of 30 patients with sound maxillary and mandibular anterior teeth free of any restorations, extrinsic stains and caries were included. Measurements were taken with Vernier Caliper. For teeth measurement, internal Jaws of Vernier Caliper were used to avoid lip distortion. Every tooth was measured (mesially, distal, and midway), and the mean was obtained. Results: The average age of patients were 25.13±3.19 years with 40% male and 60% female. On right side of Arch, mean visibility of maxillary central incisor was 1.77±0.25mm, lateral incisor 1.24±0.18mm, and canine 0.41±0.09mm and mean visibility of mandibular central incisor was 1.49±0.27mm, lateral incisor 1.50±0.26mm and canine was 0.85±0.27mm. Similarly, on left side of Arch mean maxillary central incisor visibility was 1.77±0.25mm, lateral incisor 1.29±0.21mm, and canine 0.43±0.06mm and mean mandibular central incisor visibility was 1.48±0.24mm, lateral incisor 1.51±0.26mm and canine was 0.88±0.27mm respectively. Conclusion: For treatment planning in esthetic zone we should follow some fundamental guidelines. It is important during replacement or even during restoration of maxillary and mandibular anterior teeth, to consider dento-facial specificities of each person and different natural teeth proportions.